Diagnostic and Therapeutic Approach in Paediatric Inflammatory Bowel Diseases: Results from a Clinical Practice Survey - Bronsky, Jiri; de Ridder, Lissy; Ruemmele, Frank M; Griffiths, Anne; Buderus, Stephan; Hradsky, Ondrej; Hauer, Almuthe Christina (Journal of pediatric gastroenterology and nutrition, 2019)
OBJECTIVES: Despite existence of international guidelines for diagnosis and management of inflammatory bowel diseases (IBD) in children, there might be differences in the clinical approach. METHODS: A survey on clinical practice in paediatric IBD was performed among members of the ESPGHAN Porto IBD working group and interest group, PIBD-NET, and IBD networks in Canada and German-speaking countries (CIDsCANN, GPGE), using a web-based questionnaire. Responses to 63 questions from 106 paediatric IBD centres were collected. RESULTS: Eighty-four percentage of centres reported to fulfil the revised Porto criteria in the majority of patients. In luminal Crohn disease (CD), exclusive enteral nutrition is used as a first-line induction therapy and immunomodulators (IMM) are used since diagnosis in the majority of patients. Infliximab (IFX) is mostly considered as first-line biological. Sixty percentage of centres have experience with vedolizumab and/or ustekinumab and 40% use biosimilars. In the majority of ulcerative colitis (UC) patients 5-aminosalicylates are continued as concomitant therapy to IMM (usually azathioprine [AZA]/6-MP). After ileocaecal resection (ICR) in CD patients without postoperative residual disease, AZA monotherapy is the preferred treatment. CONCLUSIONS: A majority of centres follows both the Porto diagnostic criteria as well as paediatric (ESPGHAN/ECCO) guidelines on medical and surgical IBD management. This reflects the value of international societal guidelines. However, potentially desirable answers might have been given instead of what is true daily practice, and the most highly motivated people might have answered, leading to some bias.
Keywords: Infliximab; infliximab; lékařská praxe - způsoby provádění; Guideline Adherence; Biosimilar Pharmaceuticals; Germany; Female; dítě; pediatrie; chirurgie trávicího traktu; ženské pohlaví; průzkumy zdravotní péče; Kanada; Adolescent; Inflammatory Bowel Diseases; imunologické faktory; lidé; Německo; Digestive System Surgical Procedures; Gastroenterology; Colitis, Ulcerative; biosimilární léčivé přípravky; gastrointestinální látky; Crohn Disease; Canada; gastroenterologie; Immunologic Factors; směrnice pro lékařskou praxi jako téma; Male; Practice Guidelines as Topic; ulcerózní kolitida; idiopatické střevní záněty; Child; Crohnova nemoc; Pediatrics; mužské pohlaví; Gastrointestinal Agents; Health Care Surveys; mladiství; dodržování směrnic; Practice Patterns, Physicians'; Humans